2021
DOI: 10.1111/jfpe.13700
|View full text |Cite
|
Sign up to set email alerts
|

UV‐irradiation influence on free radical formation and radical scavenging ability of caffeic acid—EPR, UV‐Vis, and colorimetric examination

Abstract: Electron paramagnetic resonance (EPR) spectroscopy, UV-Vis spectrophotometry, and colorimetric analysis, were used to examine nonirradiated and UV-irradiated caffeic acid.In this work free radical formation during UV-irradiation of caffeic acid and the effect of UV-irradiation on its radical scavenging ability, were studied. The influence of time of UV-irradiation on these problems was evaluated. EPR spectra of free radicals in caffeic acid and 1,1-diphenyl-2-picrylo-hydrazyl (DPPH) were measured. DPPH was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Among the studied species, catechin was found to present in Carex stramentitia and C. alopecuroides, while absent in other species in our present investigation suggesting the bioactive potentiality of these native species of Carex. Similarly, caffeic acid, one of the potent polyphenolic acids also has many therapeutic potentialities such as antimetastatic, antitumor (Klein et al 2021;Sari et al 2022), anti-hyperglycemic (Oršolić et al 2021), antimutagenic effect and radical scavenging property (Bogacz et al 2021;Temviriyanukul et al 2021). Several lines of evidence showed that this phenolic acid has some physiological effects like antioxidative property (Genaro-Mattos et al 2015;Bajomo et al 2022), antiviral activity (Sinha et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Among the studied species, catechin was found to present in Carex stramentitia and C. alopecuroides, while absent in other species in our present investigation suggesting the bioactive potentiality of these native species of Carex. Similarly, caffeic acid, one of the potent polyphenolic acids also has many therapeutic potentialities such as antimetastatic, antitumor (Klein et al 2021;Sari et al 2022), anti-hyperglycemic (Oršolić et al 2021), antimutagenic effect and radical scavenging property (Bogacz et al 2021;Temviriyanukul et al 2021). Several lines of evidence showed that this phenolic acid has some physiological effects like antioxidative property (Genaro-Mattos et al 2015;Bajomo et al 2022), antiviral activity (Sinha et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…UVA radiation increases the risk of skin cancer [41]. In this work, it was assumed that the interactions of antioxidants with free radicals not only depend on their type [42][43][44][45], but also the physical factors in the environment, including UV radiation, which affect these interactions [46,47]. We searched for answers to the question of whether the tested plant raw materials can be stored with access to UVA radiation.…”
Section: Introductionmentioning
confidence: 99%